Динаміка якості життя за візуально-аналоговою шкалою PSQ у пацієнтів після дентальної одномоментної імплантації по одноетапному протоколу залежно від техніки її виконання - Нєженцев, Є. Ю.; Чертов, Сергій Олександрович; Njezhencev, Ye.Yu.; Chertov, S. O. (My University, 2024)
Вивчити якість життя в динаміці у пацієнтів після дентальної одномоментної імплантації по одноетапному протоколу залежно від техніки її виконання за візуально-аналоговою шкалою (ВАШ) PSQ. Матеріали та методи. У дослідження увійшло 56 пацієнтів, яким була проведена дентальна одномоментна імплантація по одноетапному протоколу. Залежно від техніки виконання дентальної імплантації пацієнтів було поділено на 2 групи: основну групу спостереження склали 25 пацієнтів, яким після екстракції зубу, імплантат встановлювався у підготовлене ложе з попереднім заповненням лунки ксенографтом Sensobone, після чого формували м’якотканинну манжету армовану кістковопластичним матеріалом (зону м’яких тканин заповнювали ксенографтом Sensobone та вільним сполучнотканним аутотрансплантатом) з наступною фіксацією тимчасової коронки; у групу порівняння увійшли 26 пацієнтів, яким після екстракції зубу, імплантат встановлювався у підготовлене ложе з попереднім заповненням лунки ксенографтом Sensobone, після чого заповнювали зону м’яких тканин ксенографтом Sensobone та фіксували тимчасову коронку. Для оцінки якості життя пацієнтам було запропоновано заповнити ВАШ PSQ, яку використовували до проведення імплантації, через 3 місяці та через рік після імплантації. Результати дослідження оброблені на комп’ютері з використанням статистичного пакету ліцензійної програми «Statistica, версія 13» (Copyright 1984-2018 TIBCO Software Inc. All rights reserved. Ліцензія № JPZ8041382130ARCN10-J). Study the quality of life in dynamics of the quality of life in the patients after single-step dental implantation according to a one-stage protocol depending on the technique of its implementation according to the visual analogue (VAS) PSQ scale. Materials and methods. The study comprised 56 patients who underwent single-step dental implantation according to a onestage protocol. Depending on the technique of dental implantation, patients were divided into two groups: the index group consisted of 25 patients who, after tooth extraction, had the implant placed in the prepared bed with preliminary filling of the socket with Sensobone xenograft, when a soft tissue cuff reinforced with bone grafting material was formed afterwards (the soft tissue area was filled with Sensobone xenograft and free connective tissue autograft), followed by fixation of a temporary crown. The comparison group included 26 patients who, after tooth extraction, had the implant placed in the prepared socket with preliminary filling of the socket with Sensobone xenograft, when the soft tissue area was filled with Sensobone xenograft afterwards, and a temporary crown was fixed. To assess the quality of life, patients were asked to fill out the VAS PSQ before the implantation, three-month follow-up and one year after implantation. The results of the study were processed using the statistical package of the licensed software “Statistica, version 13” (Copyright 1984-2018 TIBCO Software Inc. All rights reserved. License No. JPZ8041382130ARCN10-J).
Dynamics of quality of life according to the visualanalogue psq scale in patients after single-step dental implantation according to a one-stage protocol depending on the technique
Keywords: дентальна імплантація; якість життя; візуально-аналогова шкала PSQ; dental implantation; quality of life; visual analogue PSQ scale; single-step implantation; xenograft; connective tissue graft; socket preservation; autotransplantation